IMF Survey, Volume 37, Issue 11. (IMF Survey; IMF Survey, 2008)
World Economic Outlook Update, IMF's Future role Debated, Poor Countries Face Crisis Impact, Eastern Europe's Currency Risk, Interview with Hamad Al Suwaidi, Mideast-Central Asia Outlook, Pacific Islands Face Pressures, Interview with IMF Statistics Director, News Briefs.